2013
DOI: 10.1051/fruits/2013071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium and nitrogen fertilization on bacterial canker susceptibility in stone fruits

Abstract: Original article Fruits, vol. 68 (3) Effect of calcium and nitrogen fertilization on bacterial canker susceptibility in stone fruits. Abstract -Introduction. Bacterial canker, caused by Pseudomonas syringae pv. syringae, is a destructive disease where stone fruit trees are cultivated. The efficacy of nitrogen and calcium fertilization on bacterial canker susceptibility was evaluated in stone fruits. Materials and methods. Field experiments were conducted to study the efficacy of foliar applications of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…It has long been recognized that the nutritional status of a plant can play a role in its susceptibility to pathogenic fungi. Studies have shown how nitrogen fertilization may aggravate the incidence of some diseases (Heier et al, 2005;Santos et al, 2009;Hemissi et al, 2018), but the incidence of other diseases seems to be mitigated by good plant nutritional status (Lecompte et al, 2010;Cao et al, 2013;Krnjaja et al, 2015;Zimerman-Lax et al, 2016). In this study it was not possible to establish a relationship between olive anthracnose and nitrogen rates in any of the cultivars.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has long been recognized that the nutritional status of a plant can play a role in its susceptibility to pathogenic fungi. Studies have shown how nitrogen fertilization may aggravate the incidence of some diseases (Heier et al, 2005;Santos et al, 2009;Hemissi et al, 2018), but the incidence of other diseases seems to be mitigated by good plant nutritional status (Lecompte et al, 2010;Cao et al, 2013;Krnjaja et al, 2015;Zimerman-Lax et al, 2016). In this study it was not possible to establish a relationship between olive anthracnose and nitrogen rates in any of the cultivars.…”
Section: Discussionmentioning
confidence: 63%
“…David et al (2003) stated that nitrogen fertilization could help reduce powdery mildew (Erysiphe cichoracearum) incidence in Hiemalis begonia in the greenhouse. Cao et al (2013) reported a decreased host susceptibility to bacterial cancer (Pseudomonas syringae pv. syringae) in stone fruit species, such as peach (Prunus persica), prune (Prunus domestica) and almond (Prunus dulcis).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ca and Mg contents in plant tissue were negatively correlated with disease severity in French peach plantations (Vigouroux & Bussi, 1989). However, Cao et al (2011Cao et al ( , 2013 Even though sulfur (S) is known as a nutrient with high relevance for stress defense (Capaldi, 2015;Rausch & Wachter, 2005), little attention has been paid so far on S supply in the context of Ps infection.…”
Section: Susceptibility Of Host Plants To Ps Is Dependent On Nutrient...mentioning
confidence: 99%
“…Many studies of Ps diseases on woody species put a spotlight on other stress factors, for example, ring nematodes, acid soils, and drought (Cao et al, 2005(Cao et al, , 2013Mauri et al, 2016;Melakeberhan et al, 2000;Nyczepir et al, 2012;Vigouroux et al, 1987;Wehunt & Weaver, 1982). These factors, and thus their impact on Ps diseases, are often interlinked with nutrient supply.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation